Integrated 240 GHz dielectric sensor with DC readout circuit in THz lab-on-chip measurements - Defu Wang; Klaus Schmalz; Mohamed H Eissa; Johannes Borngraber; Maciej Kucharski; Mohamed Elkhouly; Farabi I Jamal; Minsu Ko; He, W., (2017 IEEE MTT-S International Microwave Symposium (IMS), 2017)
This paper presents a highly selective integrated dielectric sensor with read-out circuit at 240 GHz in SiGe BiCMOS and back-side etching technology. The sensor features with a resonator to perform bandpass frequency response which varied in accordance to the dielectric change of the sample under test. This variation can be sensed and recorded as the change of output voltage of an integrated 240 GHz IQ receiver. The demonstration of aforementioned function is verified by measuring the output of mixer when a sample is placed over the resonator.